2020
DOI: 10.1007/s00266-020-01789-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Plastic Surgery Residency Training

Abstract: Nowadays didactic and surgical activities for residents in the surgery field are less and less due to an increasing burden of documentation and ''non-educational work.'' Considering the current lockdown due to the COVID-19 pandemic, it has never been so important to find different ways to allow residents to improve their knowledge. We asked all plastic and esthetic surgery residents in our country to fill out a questionnaire to investigate changes in their didactical activity and analyze problems about their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 4 publications
3
101
0
4
Order By: Relevance
“…"Touch Surgery" application has a wide range of surgeries, with 42 of them being plastic surgeries. 14 The Impact of COVID-19 on Plastic Surgery Training and Practice Dharini et al Abbreviations: OPD, outpatient department; PPE: personal protective equipment.…”
Section: To Preserve Surgical Skillsmentioning
confidence: 99%
“…"Touch Surgery" application has a wide range of surgeries, with 42 of them being plastic surgeries. 14 The Impact of COVID-19 on Plastic Surgery Training and Practice Dharini et al Abbreviations: OPD, outpatient department; PPE: personal protective equipment.…”
Section: To Preserve Surgical Skillsmentioning
confidence: 99%
“…13 In another survey, more than 60% of plastic surgery residents stated that cutbacks to didactics and practical training would affect their training and professional experience significantly. 14 Although some surveys demonstrate the resilience of program directors and trainees, others reflect the challenges perceived during this pandemic. For example, a survey of head and neck surgery program directors indicated that 86% felt that their fellows were ready to enter practice, 15 whereas a survey of 81 head and neck surgery trainees reported that although most felt prepared to practice, only 57% had secured full-time positions and 10% had a pending position put on hold because of hiring freezes.…”
mentioning
confidence: 99%
“…The impact of COVID-19 on mental health is undeniable. 1 , 4 The uncertainty and novelty of this situation creates anxiety and stress that affects trainees’ daily lives and those of their family and friends. Thus, activities to promote physical and mental wellbeing are paramount.…”
Section: Physical and Mental Wellbeingmentioning
confidence: 99%
“…Numerous strategies have been implemented to optimize education and well-being: team restructuring, clinical reassignment, reduced hospital visits and creation of virtual curriculums. 1 , 2 , 3 , 4 , 5 …”
mentioning
confidence: 99%